THE CONCEPT OF DESERT TOURISM AND ITS TYPES - Usmanov, Marufdjan Rustamovich; Suyarova, Nargiza Ashurovna (SCIENCE and SOCIETY, 2026)
The article discusses some types of tourism, especially the characteristics of desert tourism, its forms, integration with other types of tourism, natural geographical aspects. In addition, the prospects and opportunities for the development of desert tourism and the factors of its formation are described.
Keywords: tourism; desert tourism; economy; territory; types of tourism; landscape